Pendeteksi Kesegaran Buah Menggunakan Sensor Warna dan Kelembaban - Iwan Fitrianto Rahmad (JURIKOM (Jurnal Riset Komputer), 2019)
One of the stages in processing plantation products is product sorting based on quality (for example freshness of fruit). The fruit sorting process still uses the manual method, while this method is often inaccurate and the results vary, due to different perceptions from each person. This freshness detection tool can determine fresh fruit or less fresh fruit and can also detect rotten fruit, using a color sensor and humidity sensor, where the color sensor used to determine the freshness of fruit, which is applied is climacteric and non-fruit - important period . The fruit is put in a lighted box. The determined light will be captured by the sensor with a certain light intensity value which will then be forwarded to the TSC3200 color sensor. Electronic components used in addition to the TSC3200 color sensor are DHT11 and Arduino humidity sensors to process data that includes the results of the color and humidity sensors